Answer:
If your asking what the sum of the yards is it would be -1
Step-by-step explanation:
First I would make a number line from -10 to positive 10. Then from zero add nine. Then subtract 10 from 9. Since 10 is bigger than nine it would be a negative number. Hope this helped.
Answer: She would have to burn between 220 and 240 calories per minute to have a calorie burn rate between those of Martin and Paul.
Step-by-step explanation:
Martin:
360 calories / 30 min = 12 calories/min
Paul:
165 calories / 15 min = 11 calories/min
Kara:
Needs to burn between 11 and 12 calories/min, so we'll calculate the range:
11 calories/min x 20 min = 220 calories (minimum # calories she can burn)
12 calories/min x 20 min = 240 calories (maximum # calories she can burn)
Answer: Approximately 4 deaths per minutes.
Step-by-step explanation:
Since, 1 year = 365 days,
1 day = 24 hours,
1 hour = 60 minutes,
⇒ 1 year = ( 365 × 24 × 60 ) minutes = 525600 minutes,
If the numbers of deaths in one year = 2.2 million = 2200000
⇒ The numbers of deaths in 525600 minutes = 2200000
⇒ The number of deaths in 1 minute = 2200000/525600 = 4.18569254186 ≈ 4
Hence, There are approximately 4 deaths per minutes.
Answer:
Step-by-step explanation:
To answer this question, we have to sum each pair of cable and see which one results in 20/24.
Now, if we simply 20/24, we have:
As you can see, the answer is the second sum above, because they have the same basic fraction.
Therefore, the answer is
Answer:
3/6 + 1/3
Step-by-step explanation:
20/24 can be devided top and bottom by 4 which would equal 5/6, if you add 3/6 + 1/3 also equals 5/6.
Answer:
The decimal quantity of the flour Amelia used to bake the cake is 0.95 pound.
Step-by-step explanation:
Amelia used 19/20 pounds of flour to bake a cake.
We have to write the quantity of flour she used in decimal form.
To write in decimal form, we will divide 19 by 20.
So, the decimal quantity of the flour Amelia used to bake the cake is 0.95 pound.
Answer:
Step-by-step explanation:
(3+1)/(9-1) = 4/8 = 1/2
y + 1 = 1/2(x -1)
y + 2/2 = 1/2x - 1/2
y = 1/2x - 3/2